Deaminated purine bypass by DNA polymerase η - Andreeva, Antonina (Biochem J, 2021)
A recent work by Jung and colleagues (Biochem J. 477, 4797–4810) provides an explanation of how DNA polymerase η replicates through deaminated purine bases such as xanthine and hypoxanthine. This commentary discusses the crystal structures of the polymerase η complexes that implicate the role of tautomerism in the bypass of these DNA lesions.